Dendrochronology and dendroclimatology of tropical tree species from southeastern Peruvian Amazon - Portal Cahuana, Leif Armando (2022)
The tropical forests of South America have high biodiversity, however their extension and their characteristics make their conservation very complicated, this happens in all the countries that comprise it and Peru is no stranger to this reality, so research is required oriented to the conservation of its forests and that helps sustainable forest management, minimizing its impacts, with technical and scientific information according to its reality. The study of growth rings through dendrochronology is an important tool to help with information that helps manage forests quickly and economically. That is why the main objective is to analyze the tropical species of the Amazon rainforest in Southeast Peru for dendrochronological and dendroclimatic studies, for which a history of the art of dendrochronology in Peru was first carried out, to have a clear idea of the advances and the challenges of this science in the country, then the potential of the growth rings of 34 forest species was analyzed for dendrochronological studies in the Madre de Dios region (MDD), a tri-border region with seasonal climate, carried out from a sample by species, then, finally, the dendrochronology of six MDD species was studied, where a total of 181 trees of the six species and 04 samples for each tree were collected. In general, the procedure was to dry the samples at room temperature, then sanded-polished and finally scanned the cross- sections to measure the growth rings, be characterized and build the chronologies of the species studied. The results obtained are: there is a review article that shows the state of the art of dendrochronology in Peru and, among other things, future challenges are raised. About the potential of the growth rings of 34 species, 82% presented very visible and moderately visible rings (28). Regarding the dendrochronological study of the six species, acceptable statistics were obtained and it was possible to build three chronologies of more than 200 years, the species were influenced by the local climate (precipitation) in the rainy season and the anomalies of the SST sea temperature of the Pacific and Atlantic oceans, highlighting the influence of the El Niño phenomenon on the growth of species. These results highlight the need to understand how forest species are coping with climate change in tropical forests. This knowledge is key to applying it to forest management and the conservation of tropical forests.